The Design of Instruments for Government Finance in an Islamic Economy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper presents perhaps the most viable approach for the design of an instrument of government finance (and monetary management) in an Islamic economy where conventional transactions based on an ex-ante promise of a risk-free rate of return are forbidden. Resources to finance government infrastructural and development projects can be mobilized by issuing a national participation paper and this instrument can also serve as an instrument of monetary management. The paper discusses various conceptional issues underpinning the introduction of such an instrument and methods of calculating a corresponding rate of return. In principle, this approach has been accepted by the Islamic Republic of Iran.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet